2004
DOI: 10.1177/0013124504268454
|View full text |Cite
|
Sign up to set email alerts
|

Structural Inequities and the Achievement Gap in Urban Schools

Abstract: If teachers represent a child’s most important asset, they also can be a child’s greatest liability, especially in states where a shortage of well-qualified teachers impedes the academic progress of African American students in learning contexts. The author asserts that a transformation in practices must occur in teacher education programs if these programs are to become places where preservice candidates learn to adopt pedagogies that are instrumental in the academic achievement of African American students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Cammarota and Romero (2006) state that educators attend to students overall well-being when they connect with students on an emotional level by (a) providing reciprocal opportunities to share their lives, (b) demonstrating compassion for the dehumanizing experiences students of color encounter, and (c) situating learning in social issues that are relevant to the experiences of marginalized communities. Additionally, Talbert-Johnson (2004) adds that schools should be "places where students of color feel their full humanity is visible and cherished by their teachers" (p. 32). The authors suggest that students' full humanity is honored when educators affirm students' ambitions and assist students in dealing with obstacles to their ambitions.…”
Section: : the Full Development Of The Person Is Essential For Humanmentioning
confidence: 99%
“…Cammarota and Romero (2006) state that educators attend to students overall well-being when they connect with students on an emotional level by (a) providing reciprocal opportunities to share their lives, (b) demonstrating compassion for the dehumanizing experiences students of color encounter, and (c) situating learning in social issues that are relevant to the experiences of marginalized communities. Additionally, Talbert-Johnson (2004) adds that schools should be "places where students of color feel their full humanity is visible and cherished by their teachers" (p. 32). The authors suggest that students' full humanity is honored when educators affirm students' ambitions and assist students in dealing with obstacles to their ambitions.…”
Section: : the Full Development Of The Person Is Essential For Humanmentioning
confidence: 99%
“…Success here is perhaps not measured in terms of grades (which are notoriously low) but in terms of inspection reports, awards, and the fact that they have a constant inflow of newly arrived refugees (Skolverket, 2004;Statens Offentliga Utredningar, 2006). Additional problems are created by the lack of trust in pedagogical content and educational standards as well as the low expectations that teachers in the upper-secondary schools have toward students with an urban school background (Finn & Cox, 1992;Nelson, Palonsky, & McCarthy, 2004;Talbert-Johnson, 2004).…”
Section: Settings and Methodsmentioning
confidence: 99%
“…He used to like use the blocks to explain it and keep going over it so we could know. Talbert-Johnson (2004) reported that a well-qualified teacher can be the single most powerful variable affecting student performance in schools. Uhlenberg and Brown (2002) stated that teachers represent the front line in education.…”
Section: Themementioning
confidence: 99%